Impact of thrombus burden on procedural and mid-term outcomes after primary percutaneous coronary intervention. Issue 3 (May 2016) - Martí, David; Salido, Luisa; Mestre, José L.; Esteban, María J.; Casas, Eduardo; Jiménez-Mena, Manuel; Pey, Jaime; Sanmartín, Marcelo; Hernández-Antolín, Rosana; Zamorano, José L.
Abstract : Objective: Angiographic thrombus burden (TB) can be assessed early and enable a decision on intervention. The aim of this study was to analyze its effect on the incidence of cardiac events after a primary percutaneous coronary intervention. Patients and methods: We carried out a prospective study of 480 consecutive ST-segment elevation myocardial infarction patients treated by systematic primary percutaneous coronary intervention. Large TB was defined as thrombus length at least 2 vessel diameters or as solid thrombus obtained through catheter aspiration. The primary outcome measure was a composite of death, reinfarction, or target vessel revascularization. Results: A total of 205 (47%) patients fulfilled the criteria for large TB. These patients were more frequently treated with abciximab (62.0 vs. 35.8%, P <0.001), showed more angiographic complications (26.6 vs. 13.7%, P =0.001), and had larger infarcts (peak troponin I, 74 vs. 50 ng/ml, P =0.015). During a follow-up of 19±5 months, the rates of primary outcome were similar between groups of small and large TB (16.2 vs. 12.8%, hazard ratio: 0.88, 95% confidence interval: 0.46–1.67, P =0.691). There were no differences in the rates of definite stent thrombosis (0.5 vs. 2.2%, P =0.190). Conclusion: Large TB is associated with larger infarct size, but not with worse mid-term outcomes. Selective use of adjuvant therapies according to TB may be an effective approach to reduce thrombotic complications.